Формирование контура изображения с помощью набора вейвлет-функций - Моисеенко, А. В.; Шалимова, Ю. С.; Калашников, В. В. (ХНУРЕ, 2011)
The way of image edge extraction based on continuous wavelet transform is considered. Comparison of object edge extraction by different wavelet functions is performed.
Keywords: формирование контура изображения; контур